Trials of Freedom: African American Deserters during the U.S. Civil War. (25th August 2015) - Lande, Jonathan
Abstract: In the tumultuous war years of 1861 to 1865, enslaved men, women, and children across the United States emancipated themselves. Nearly 180, 000 African American men, including thousands of former slaves, joined the Union Army to fight for their freedom and for the nation. Historians tell the story of these brave men as one of glory. Indeed, it was glorious. Despite unequal pay and racist officers, black men fought valiantly and earned their freedom. However, this history does not capture the whole story. Experiencing freedom for the first time, many black soldiers discovered the discipline and racism of the army reminiscent of bondage and reacted angrily. Sometimes they rebelled as runaways had during enslavement—they ran. They deserted the army and its injustices to forge a freedom worth living. The army captured many African Americans deserters, though, and tried them in the courts-martial. White officers enforced enlistment contracts in the courts-martial, imposing boundaries on freedom. Capturing another angle of emancipation in the army, the trials of freedom explored here recast service as a limiting—not liberating—experience.